ChemInform Abstract: Synthesis of Substituted Exo‐Glucals via a Modified Julia Olefination and Identification as Selective β‐Glucosidase Inhibitors. Issue 27 (8th July 2014) - Habib, Samuel; Larnaud, Florent; Pfund, Emmanuel; Mena Barragan, Teresa; Lequeux, Thierry; Ortiz Mellet, Carmen; Goekjian, Peter G.; Gueyrard, David
Abstract A series of fluorine and non‐fluorine‐substituted C‐glucosylidenes (III)/(IV) is synthesized as mixtures of (E)/(Z)‐isomers via a modified Julia olefination.